Scanning Ion-Conductance Microscopy for Studying β‑Amyloid Aggregate Formation on Living Cell Surfaces - Kolmogorov, Vasilii S.; Erofeev, Alexander S.; Barykin, Evgeny P.; Timoshenko, Roman V.; Lopatukhina, Elena V.; Kozin, Sergey A.; Gorbacheva, Lyubov R.; Salikhov, Sergey V.; Klyachko, Natalia L.; Mitkevich, Vladimir A.; Edwards, Christopher R. W.; Korchev, Yuri E.; et al. (Analytical chemistry (Washington), 2023)
β-Amyloid aggregation on living cell surfaces is described as responsible for the neurotoxicity associated with different neurodegenerative diseases. It is suggested that the aggregation of β-amyloid (Aβ) peptide on neuronal cell surface leads to various deviations of its vital function due to myriad pathways defined by internalization of calcium ions, apoptosis promotion, reduction of membrane potential, synaptic activity loss, etc. These are associated with structural reorganizations and pathologies of the cell cytoskeleton mainly involving actin filaments and microtubules and consequently alterations of cell mechanical properties. The effect of amyloid oligomers on cells’ Young’s modulus has been observed in a variety of studies. However, the precise connection between the formation of amyloid aggregates on cell membranes and their effects on the local mechanical properties of living cells is still unresolved. In this work, we have used correlative scanning ion-conductance microscopy (SICM) to study cell topography, Young’s modulus mapping, and confocal imaging of Aβ aggregate formation on living cell surfaces. However, it is well-known that the cytoskeleton state is highly connected to the intracellular level of reactive oxygen species (ROS). The effect of Aβ leads to the induction of oxidative stress, actin polymerization, and stress fiber formation. We measured the reactive oxygen species levels inside single cells using platinum nanoelectrodes to demonstrate the connection of ROS and Young’s modulus of cells. SICM can be successfully applied to studying the cytotoxicity mechanisms of Aβ aggregates on living cell surfaces.